2006
DOI: 10.1080/00365520500463332
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory changes in the referred pain area before and after cholecystectomy in patients with uncomplicated gallstone disease

Abstract: Uncomplicated gallstone disease leads to significant hyperalgesia in the somatic referred pain area. At the time of the postoperative investigation none of the patients suffered from pain, which was reflected in the normal sensory findings in the previous referred pain area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In a study by Stawowy et al [31], in patients with uncomplicated gallstone disease before cholecystectomy, hypersensitivity was present only in subgroups of patients, but not on whole-group level, the most significant differences being hypersensitivity to electrical stimuli, which were not used in our study. Regarding the QST findings after 6 and 12 months, 2 follow-up studies on postoperatively pain-free patients showed no signs of hypersensitivity [21,30], thus supporting our findings. A study by Kurucsai et al [22] on patients with postcholecystectomy syndrome, tested with electrical stimuli, reported significant hypersensitivity in the RPA.…”
Section: Discussionsupporting
confidence: 91%
“…In a study by Stawowy et al [31], in patients with uncomplicated gallstone disease before cholecystectomy, hypersensitivity was present only in subgroups of patients, but not on whole-group level, the most significant differences being hypersensitivity to electrical stimuli, which were not used in our study. Regarding the QST findings after 6 and 12 months, 2 follow-up studies on postoperatively pain-free patients showed no signs of hypersensitivity [21,30], thus supporting our findings. A study by Kurucsai et al [22] on patients with postcholecystectomy syndrome, tested with electrical stimuli, reported significant hypersensitivity in the RPA.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, patients with GERD and NCCP also demonstrate increased areas of referred esophageal pain compared with healthy controls (6,7). In a well-designed study in patients pre-and postcholecystectomy, the authors showed that prior to surgery, 84% of patients had somatosensory hyperalgesia in the area of referred pain which resolved within 4 -12 wk following surgery (31).…”
Section: Discussionmentioning
confidence: 96%
“…Drewes and colleagues (5)(6)(7)31) have performed many studies looking at referred visceral pain both in health and in patients with conditions that include gastroesophageal reflux disease (GERD), noncardiac chest pain (NCCP), pancreatitis, and gallstone disease. In studies of healthy subjects it has been shown that sensitization of the esophagus with either dilute acid or capsaicin results in the expansion of the area of referred esophageal pain elicited by thermal, mechanical, and electrical stimulation (1,24).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cholecystectomy on central sensitization have been explored in non-fibromyalgic subjects in previous studies. Stawowy et al [ 32 ] applied quantitative sensory testing in the referred pain area from the gallbladder (upper abdominal quadrant) and in a control area on the contralateral side of the abdomen before and 4–12 weeks after surgery, while Kjaer et al [ 33 ] performed a similar study evaluating the somatosensory changes 2–7 years after laparoscopic cholecystectomy. In both cases the initial hypersensitivity of the referred area returned to normal in the follow-up period, also in patients who developed postcholecystectomy syndrome.…”
Section: Discussionmentioning
confidence: 99%